Everyday Lives of LGBTI in Kathmandu Valley: A Narrative Inquiry - Bhatta, Megh Vilas (Nepalese Journal of Development and Rural Studies, 2017)
There is an increasing recognition of political and socio-economic right and identification of the LGBTI throughout the world. Hereby, I soaked into lived experiences of LGBTI people and interpreted those experiences for better understanding of their daily life activities, the gap between their individual identities and social identities, prevailing exclusionary provisions and need of their social inclusion in term of gender identities and social development. The study also relates to the multiple realities of the world view of LGBTI investigated through interpretive paradigms and narrative inquiry as methodology which focuses on critical life events depicted through participants’ stories, exploring their holistic views and holds valuable potential for researchers in a broad range of socio-cultural and economic structures. The research questions; how do LGBTI perform everyday life activities, how have they been appraising their identity and why social exclusionary practices have been affecting the lives of LGBTI in the development process of Nepal have been instrumental to materialize them. Nepalese Journal of Development and Rural StudiesVol. 14 (Joint issue) (1&2), 2017, Page: 63-73